2021
DOI: 10.1002/celc.202100108
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Spectroscopy for All‐Solid‐State Batteries: Theory, Methods and Future Outlook

Abstract: Electrochemical impedance spectroscopy (EIS) is widely used to probe the physical and chemical processes in lithium (Li)-ion batteries (LiBs). The key parameters include state-of-charge, rate capacity or power fade, degradation and temperature dependence, which are needed to inform battery management systems as well as for quality assurance and monitoring. All-solid-state batteries using a solid-state electrolyte (SE), promise greater energy densities via a Li metal anode as well as enhanced safety, but their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
201
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(206 citation statements)
references
References 188 publications
(204 reference statements)
3
201
2
Order By: Relevance
“…The electronic conductivity was measured via direct current (DC) polarization technique ( Boulineau et al, 2012 ; Zhang et al, 2020 ; Vadhva et al, 2021 ). The Ni/Li 6 PS 5 Cl/Ni symmetrical cells were prepared in a similar way as previously mentioned.…”
Section: Methodsmentioning
confidence: 99%
“…The electronic conductivity was measured via direct current (DC) polarization technique ( Boulineau et al, 2012 ; Zhang et al, 2020 ; Vadhva et al, 2021 ). The Ni/Li 6 PS 5 Cl/Ni symmetrical cells were prepared in a similar way as previously mentioned.…”
Section: Methodsmentioning
confidence: 99%
“…At 60 °C, the 3(RQ) equivalent circuit model (Table S7, Supporting Information) could be simplified into the RQ model (Table S8, Supporting Information) owing to the overlapping time constants of the electrochemical processes at high temperature. [ 32 ] Therefore, the interface resistance, R int , was defined as the sum of R HF , R MF , and R LF . It was found that the R int of PAQS@CNT decreased from 1487 Ω at 25 °C to 453 Ω at 60 °C, however, still about five times as that of PTTCA@CNT (88.3 Ω).…”
Section: Resultsmentioning
confidence: 99%
“…The two semicircles in the high frequency region and medium frequency region correspond to the charge transfer resistance at cathode interfaces (R c ) and anode interfaces, respectively. [13] The equivalent circuit in Figure S19, Supporting Information, is applied for the fitting processes. The measured Nyquist plots and the simulated results are provided in 6, 32.4, 24, 34.2, 20.8, and 22.6 Ω, respectively, and the corresponding CAM mass fraction value is 50, 50, 60, 60, 70, and 70 wt%.…”
Section: Electrochemical Kinetic Evaluations Of Assbsmentioning
confidence: 99%